Continental scale body wave tomography of India: Evidence for attrition and preservation of lithospheric roots. (21st March 2014) - Singh, Arun; Mercier, J.‐P.; Ravi Kumar, M.; Srinagesh, D.; Chadha, R. K.
Abstract We assemble P and S waveforms of 2301 teleseismic earthquakes registered at 413 broadband seismic stations spanning the Indian plate from the southern tip of India to the Himalayan collision belt and generate an accurate data set of 52, 050 P and 30, 423 S arrival times through the multichannel cross‐correlation approach. These traveltimes are then inverted to obtain 3‐D P and S velocity structures of the subcontinent at a 2° × 2° lateral resolution. The heterogeneous nature of the Indian lithospheric mantle revealed in this study suggests that the lithospheric roots are not uniformly thick on a regional scale. The key cratonic segments of the Indian shield are characterized by pockets of high velocity anomalies (∼3%) at shallow depths (<300 km), with the diamondiferous regions like Wajrakarur revealing high shear wave anomalies down to ∼300 km. In contrast to the southern Deccan volcanic province (DVP), the northwestern DVP is underlain by low velocity anomalies at similar depths suggesting that the upper mantle retains imprints of Deccan volcanism which was facilitated by the reactivation of the rift systems.